Ectopic Hidradenoma Papilliferum of Axilla: A Case Report - Purbasha Misra; Samarth Shukla; Rajesh Godavarthi (Journal of Clinical and Diagnostic Research)
A benign adnexal tumour is a non cancerous growth located in the uterine tubes, ovaries, or near the uterus, including the surrounding connective tissue. While adnexal tumours can also be cancerous, they are predominantly benign. Moreover, adnexal masses can be non gynaecological, such as bladder diverticulum, appendicitis, apocrine gland tumours, sebaceous gland tumours, eccrine gland tumours and nerve sheath tumours. These tumours can occur at any age due to various causes. Some adnexal tumours are sporadic, while others may be linked to conditions such as Brooke-Spiegler syndrome and Birt-Hogg-Dubé syndrome. The tumours can be solid or fluid-filled and while some resolve spontaneously, others require therapy or surgical intervention. This case describes one such benign adnexal tumour: hidradenoma papilliferum, or papillary hidradenoma, which is a rare subcutaneous benign adnexal tumour of the apocrine glands in the anogenital regions. It typically occurs in females aged 30 to 50 years but is rarely reported in males. Hidradenoma papilliferum that is localised outside the anogenital region is referred to as ectopic. Ectopic presentations are primarily reported in the head and neck regions, especially on the external ear and eyelid, where modified apocrine glands are present. It is rarely reported in the nose, arm and axilla. This case report details a 53-year-old female who presented to the Surgery Outpatient Department (OPD) with a small swelling in her axilla accompanied by mild pain. Histopathological examination confirmed the nodular lesion as hidradenoma papilliferum. The location of the tumour was extremely rare and is often misdiagnosed as syringocystadenoma papilliferum and trichoepithelioma.